Effects of adsorption properties and mechanical agitation of two detergent cellulases towards cotton cellulose - Caparrós Vásquez, Cristina Maria (2012)
The impacts of two hybrid cloned commercial cellulases designed for detergency on cotton fibres were compared. HiCel45 has a family 45 catalytic domain and a fungal cellulose binding module (CBM) from the fungus Humicola insolens. BaCel5 has a family 5 catalytic domain and a fungal CBM from Bacillus spp. BaCel5 bound irreversibly to cellulose under the buffer conditions tested while HiCel45 was found to bind reversibly to cellulose because it showed low adsorption. BaCel5 seems to yield more activity towards cotton than HiCel45 under mild stirring conditions, but under strong mechanical agitation both enzymes produce similar amount of sugars. HiCel45 had a more progressive production of residual reducing ends on the fabric than BaCel5. These studies seem to indicate that HiCel45 is a more cooperative enzyme with detergent processes where high mechanical agitation is needed.